The Political Transformation of the Muslim Brotherhood in Jordan: From Social Movement to Parliamentary Opposition Force - Siska Anggrianto; Muhammad Wildan (Universitas Islam Negeri Sunan Kalijaga, 2025)
The Muslim Brotherhood is one of the modern Islamic movements that has had a significant influence on political and social dynamics in the Middle East. Founded in 1928 in Egypt, the organization developed in response to Western colonialism and the disintegration of the Islamic world after the collapse of the Ottoman Empire. The spread of Islamic reform ideas and the da'wah activities of the Muslim Brotherhood reached Transjordan, where it was officially established in 1945. In its early stages, the organization focused on da'wah, education, and social services, which gave it strong legitimacy among the Jordanian people. The transformation towards political involvement began to strengthen after their success in the 1989 elections, followed by the establishment of the Islamic Action Front (IAF) in 1992 as its official political representation. This study analyzes the dynamics of the development of the Muslim Brotherhood in Jordan during the period 1989–2013 and examines the impact of government policy after the 2024 elections on the organization's position. This study shows that the Muslim Brotherhood in Jordan is an example of the adaptation of Islamic movements to democratic political mechanisms as well as a response to the state's ever-changing regulations.